Dinamika Literasi dalam Kehidupan Masyarakat Pedesaan: Studi Fenomenologi tentang Pemahaman dan Pengalaman Literasi di Desa Padang Sipirok - Muhammad Iskandar Dalimunthe; Mesiono Mesiono (Jurnal Pustaka Ilmiah, 2026)
This study aims to examine the dynamics of literacy in rural communities and to understand how people perceive and experience literacy practices in their daily lives in Padang Sipirok Village. Literacy is a fundamental ability that plays an important role in improving the quality of human resources and supporting the development of community knowledge. However, literacy levels in rural communities still face several challenges, particularly related to access to information sources and the availability of literacy facilities. This condition can also be found in the community of Padang Sipirok Village, where social and cultural characteristics influence how people understand and utilize literacy in their daily activities. This research employed a qualitative, phenomenological approach to explore the community's subjective experiences regarding literacy. The findings show that the community’s understanding of literacy extends beyond reading and writing skills to include the ability to obtain and understand information from various sources. The community accesses information through social interaction, smartphones, and social media. Furthermore, literacy plays an important role in the social life of rural communities, particularly in increasing knowledge, broadening perspectives, and supporting decision-making in everyday life. Therefore, strengthening rural community literacy requires supporting the development of literacy facilities and sustainable literacy programs.